2022
DOI: 10.1111/1471-0528.17354
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of COVID‐19 vaccine in pregnant women: A systematic review with meta‐analysis

Abstract: Background There are limited data regarding COVID‐19 vaccination during pregnancy. Objectives To evaluate the effects of COVID‐19 vaccination received during pregnancy on SARS‐CoV‐2 infection, COVID‐19‐related hospitalisation, COVID‐19‐related intensive care unit (ICU) admission and maternal–fetal complications. Search strategy MEDLINE, CINHAL, Embase, Scopus and CENTRAL databases, as well as ClinicalTrials.gov , re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“… 24 A recent meta-analysis showed a reduction of SARS-CoV-2 infection and COVID-19-related hospitalization among fully vaccinated pregnant women. 25 The close-to-null association between SARS-CoV-2 infection and COVID-19 vaccination in our study could be due to the substantially lower incidence of ICU admission and vaccination rates in early pregnancy in South Korean pregnant women than in other populations.…”
Section: Discussionmentioning
confidence: 48%
“… 24 A recent meta-analysis showed a reduction of SARS-CoV-2 infection and COVID-19-related hospitalization among fully vaccinated pregnant women. 25 The close-to-null association between SARS-CoV-2 infection and COVID-19 vaccination in our study could be due to the substantially lower incidence of ICU admission and vaccination rates in early pregnancy in South Korean pregnant women than in other populations.…”
Section: Discussionmentioning
confidence: 48%
“…Pregnant women were at higher risk of COVID-19-related complications than their non-pregnant counterparts [ 19 , 20 ]. To date, no significant adverse outcomes have been found in pregnant women after COVID-19 vaccination [ 21 ]. Conversely, epidemiological studies have suggested that COVID-19 vaccination of pregnant women was very effective in preventing severe SARS-CoV-2 infection and adverse pregnancy outcomes, such as spontaneous abortion, stillbirth, and premature delivery [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some data have identified risk factors for more severe illness: Vaccination status for SARS-CoV-2 (ie below specific section) ( Tormen et al, 2023 ). As in general population: maternal age (relative risk for age > 35 years 1.42 [95 % CI, 1.13–1.8]), obesity (relative risk for BMI > 30 1.89 [95 % CI, 1.38–2.58]), or co-morbidities such as chronic cardiac or pulmonary disease, preexisting hypertension (relative risk 2.36 [95 % CI, 1.54–3.4]), diabetes mellitus (relative risk 2.12 [95 % CI, 1.27–3.25]), chronic renal disease, malignancy, and immunosuppression increase the risk of complications from COVID-19 ( Allotey et al, 2020 , McClymont et al, 2022 , Bloise et al, 2021 ).…”
Section: Maternal Complicationsmentioning
confidence: 99%